6 - Politics, Etiquette, and the Fight Against HIV/AIDS in Kenya: Negotiating for a Common Front: DOI: 10.4314/ad.v29i4.22209 - Kwena, Zachary Arochi (Africa Development, 2004)
HIV/AIDS is the single most serious socio-economic and health problem af fecting Kenya presently. The rapid spread of the epidemic resulted from the failure of government to recognise it as a problem early enough and institute necessary measures to counter it. Today, there are efforts from various stakeholders to slow down the spread of the epidemic. Some of these efforts have caused much debate and controversy, sometimes taking a political angle. Hardly any agreed steps are accepted by national institutions and even individu als on how to tackle the epidemic. This diversity of views and standpoints may be healthy especially when it comes to finding concrete solutions to the prob lem. However, this is only so if unity in diversity is achieved within a certain time-frame before the problem gets out of hand. This paper tries to assess the efforts and methods suggested in the fight against HIV/AIDS in Kenya and the resultant controversies, debates and chances for unity in diversity.